Design Of Detection System With Motion Sensor And Notification On Android Based On Arduino Microcontroller : Rancang Bangun Sistem Deteksi Dengan Sensor Gerak Beserta Notifikasi Pada Android Berbasis Mikrokontroler Arduino - Rizky Ndaru Wicaksono; Hindarto (Academia Open, 2020)
The rapid development of technology nowadays makes people want to always be creative and triggers to create something that is needed to create a security system, because of today's economy makes many people act criminally by robbery or theft. An alternative security system that is often used today is to use CCTV (Closed Circuit Television), but the limitations in conducting CCTV control include that it still has to be monitored directly at the monitoring location only. From the problems that occur, the authors develop a thesis that is able to control and monitor by sending realtime alerts in the form of notifications to the user on an Android Smartphone device by building an IoT (Internet of Thing) based detection system using a PIR (Passive Infrared) motion sensor entitled "Design And Build A Detection System With Motion Sensor And Notification On Android Based On Arduino Microcontroller".